Intellectual endogamy in the university: The neoliberal regulation of academic work. Issue 2 (1st June 2019) - Muñoz-García, Ana Luisa
Abstract : This article aims to analyse the multiple ways in which the neoliberal regulation of knowledge is negotiated by returning Chilean scholars. The data gathered suggest the construction of knowledge is highly regulated by a principle of intellectual endogamy. Intellectual endogamy is characterised by conservatism, reflected in a lack of diversity in research themes and problems and maintained by a peer-review system that controls scholars' access to research funds. However, it is also characterised by instrumentalism, which is reflected in the requirements for obtaining research funds, such as publications in indexed journals and discourses of efficiency and productivity. Both facets engender a neoliberal regulation of academic work. This research encourages an expansion of the conversation about how academic mobility affects knowledge construction.